Utilization of Fucoidan Based on Nanodelivery in Health Promotion Perspective, Molecular Mechanism, and Community Empowerment: A Scoping Review - Francisca Diana Alexandraa; Muh. Nassrum Massi; Yanti Leman; Marianti A. Manggau; Agnes Frethernety; Ira Jayanti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Fucoidan is a sulfated polysaccharide derived from brown algae with proven anticancer, antioxidant, and immunomodulatory properties. However, its clinical utilization remains limited due to high molecular weight and low bioavailability. Recent advances in nanodelivery systems provide promising strategies to overcome these limitations and align with community-based health promotion initiatives. Methods: This scoping review adopted the PEOS framework (Population, Exposure, Outcome, Study Design) and PRISMA flow to map current evidence on fucoidan’s molecular mechanisms, nanocarrier innovations, and community empowerment perspectives. Literature searches were conducted in PubMed, ScienceDirect, EBSCO, and Google Scholar from 2015–2023 using keywords “fucoidan,” “nanoparticle,” “nanocarrier,” “molecular mechanism,” and “health promotion.” Twenty-three eligible articles were critically appraised using Hawker’s Quality Assessment Tool. Results: Fucoidan exhibits anticancer effects through upregulation of Bax, downregulation of Bcl-2, activation of caspases, and inhibition of angiogenesis via NF-?B, MAPK, and Nrf2 signaling pathways. Nanodelivery systems including chitosan fucoidan nanoparticles, PEGylated PLGA, hydrogels, and microneedle patches enhanced stability, absorption, and targeted efficacy. Preclinical studies demonstrated tumor inhibition, wound healing, and immunomodulatory benefits. From a public health perspective, fucoidan-based nanotechnology supports health promotion through increased scientific literacy, integration into Health Promoting Hospitals, and economic empowerment of coastal communities producing brown algae. Conclusion:Fucoidan represents a multifunctional bioactive compound whose efficacy is strengthened by nanodelivery innovation. Integrating molecular insights with health promotion and community empowerment creates a sustainable model linking biotechnology, preventive health, and local economic development. This review emphasizes the importance of interdisciplinary collaboration in translating marine biopolymers into accessible, evidence-based complementary therapies.